Ultrasonography - A viable tool for airway assessment - Preethi B Reddy; Pankaj Punetha; Kolli S Chalam (Indian Journal of Anaesthesia, 2016)
Background and Aims: Accurate prediction of the Cormack-Lehane (CL) grade preoperatively can help in better airway management of the patient during induction of anaesthesia. Our aim was to determine the utility of ultrasonography in predicting CL grade. Methods: We studied 100 patients undergoing general endotracheal anaesthesia. Mallampati (MP) class, thyromental distance (TMD) and sternomental distance (SMD) were noted. Ultrasound measurements of the anterior neck soft tissue thickness at the level of the hyoid (ANS-Hyoid), anterior neck soft tissue thickness at the level of the vocal cords (ANS-VC) and ratio of the depth of the pre-epiglottic space (Pre-E) to the  distance from the epiglottis to the mid-point of the distance between the vocal cords (E-VC) were obtained. CL grade was noted during intubation. Chi-square test was employed to determine if there was any statistical difference in the measurements of patients with different CL grades. Sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV) and accuracy were calculated for the various parameters. Results: The incidence of difficult intubation was 14%. An ANS-VC >0.23 cm had a sensitivity of 85.7% in predicting a CL Grade of 3 or 4, which was higher than that of MP class, TMD and SMD. However, the specificity, PPV and accuracy were lower than the physical parameters. The NPV was comparable. Conclusion: Ultrasound is a useful tool in airway assessment. ANS-VC >0.23 cm is a potential predictor of difficult intubation. ANS-Hyoid is not indicative of difficult intubation. The ratio Pre-E/E-VC has a low to moderate predictive value.